To B or Not to B: Understanding B Cell Responses in the Development of Malaria Infection - Silveira, Eduardo L. V.; Dominguez, Mariana R.; Soares, Irene S. (Frontiers in Immunology, 2018)
Malaria is a widespread disease caused mainly by Plasmodium falciparum (Pf) and Plasmodium vivax (Pv) protozoan parasites. Depending on the parasite responsible for the infection, high morbidity and mortality can be triggered. In order to escape host immune responses, Plasmodium parasites disturb the functionality of B cell subsets among other cell types. However, some antibodies elicited during malaria infection have the potential to block pathogen invasion and dissemination into the host. Thus, why is protection not developed and maintained after primary parasite exposure? In this review, we discuss different aspects of B cell responses against Plasmodium antigens during malaria infection. Because most studies have focused on the quantification of serum antibody titers, those B cell responses have not been fully characterized. However, in order to secrete antibodies, a complex cellular response is set up, including not only the activation and differentiation of B cells into antibody-secreting cells, but also the participation of other cell subsets in germinal center reactions. Therefore, a better understanding of how B cell subsets are stimulated during malaria infection will provide essential insights towards the design of potent interventions.